Bulevirtide in the Treatment of Hepatitis Delta: Drug Discovery, Clinical Development and Place in Therapy - Soriano, Vicente; Moreno-Torres, Víctor; Treviño, Ana; Corral, Octavio Jorge; de Mendoza, Carmen (Drug Design, Development and Therapy, 2023)
It has been ten years since the identification of NTCP as the cell surface receptor for HBV and HDV entry into hepatocytes. The search for molecules interfering with the binding of NTCP and HBV/HDV led to design bulevirtide (BLV). This large polypeptide mimics a region of the pre-S1 HBsAg and blocks viral entry by inhibitory competition. BLV was initially tested in cell cultures, animal models and more recently in Phase I–III human trials (called ‘MYRS’). As monotherapy or in combination with peginterferon, BLV is well tolerated and exhibits potent antiviral activity. Plasma viremia significantly declines and/or becomes undetectable in more than 75% of patients treated for >24 weeks. However, serum HBsAg concentrations remain unchanged. No selection of BLV resistance in HBV/HDV has been reported in vivo to date. BLV is administered subcutaneously once daily at doses between 2 and 10 mg. BLV received conditional approval in Europe in 2020 to treat chronic hepatitis delta. The advent of peginterferon lambda or new specific anti-HDV antivirals (lonafarnib, etc.) will open the door for combination therapies with BLV. Since there is no stable reservoir for HDV-RNA within infected hepatocytes, viral clearance might be achieved using antivirals for a minimum timeframe. This is what happens in hepatitis C combining several antivirals, curing nearly all patients treated for 3 months. Clearance of HDV-RNA genomes may occur despite HBV persistence as cccDNA or chromosome integrated HBV-DNA within hepatocytes. This is supported by cases of HDV elimination using BLV despite persistence of serum HBsAg. Another path for HDV cure will derive from achieving HBsAg clearance, the goal of new promising anti-HBV gene therapies (bepirovirsen, etc.). In summary, the advent of BLV has triggered a renovated interest for antiviral therapy in hepatitis delta. We envision combination therapies that will lead to HDV cure in the near future.
Keywords: bulevirtide; hepatitis B functional cure; hepatitis delta; lonafarnib; MYR trials; peginterferon lambda; tenofovir; Scopus; JCR